Proposals for a pilot project to promote the integration of the hanseniasis patient into society - T. F. FRIST (Hansenologia Internationalis, 1976)
After a year-long study of the Baum region in the Brazilian state of São Paulo, the author found 8 basic and interdependent obstacles and comment which hamper the integration of the hanseniasis patient into society. These obstacles are: 1. The lack of a central authority to control integration activities in the region. 2. The lack of basic dogmas and guidelines on which to build a rehabilitation program. 3. The inadequate use of educational resources. 4. The lack of integration of hanseniasis work in the general medical care system. 5. The low quality of basic medical care for the hanseniasis patients. 6. The lack of socio-economic support systems for the hanseniasis patient in his community. 7. The large number of patients in Lauro de Souza Lima (the area's dermatological hospital) interned for non-justifiable reasons. 8. The presence of a growing settlement of hanseniasis patients on the outskirts of Lauro de Souza Lima. 9. Some comments on the structure and function of the pilot project. Each of these obstacles is briefly discussed and suggestions are then given for a coordinated program to overcome them.